Режими вставки постійного струму з повністю керованими тиристорами - Федів, Євген Ігорович; Сівакова, Ольга Михайлівна (Національний технічний університет "Харківський політехнічний інститут", 2019)
Проведено аналіз недоліків регулювання потоків потужності в електричних мережах та системах за допомогою проміжних ланок постійного струму, які базуються на перетворювачах струму з природною комутацією тиристорів. Показана можливість роботи перетворювачів в режимах з генерацією реактивної потужності зсуву в мережу змінного струму. Режим штучної комутації вентилів, за якого перетворювачі працюють з випереджувальним струмом, досягається закриванням тиристорів раніше природного моменту часу їх закривання. Проведено аналіз електромагнітних процесів в усталеному режимі роботи силового статичного перетворювача струму, виконаного за трифазною мостовою схемою з повністю керованими тиристорами в режимах випрямляча та залежного інвертора, які можуть бути використані для побудови проміжної ланки постійного струму, як компоненти гнучких систем пересилання змінного струму з можливостями чотириквадрантного регулювання міжсистемного обміну потужності. Наведено аналітичні вирази, які можуть бути використані для обчислення основних енергетичних характеристик вставки постійного струму в режимах керованої комутації тиристорів.

The analysis has been carried out on the disadvantages of regulating power flows in electric networks and systems using intermediate DC links, which are based on traditional current sourced converters with natural switching thyristors. It has been noted that due to modern advances in the field of power electronics, power static current sourced converters can operate in the modes with leading current, i.e. not consuming, but generating reactive shear power. The possibilities of phase regulation of the converter by the thyristors have been shown, in which the power converter can operate in the modes with the generation of reactive shear power into an alternating current network. The mode of the artificial switching of the valves, in which the converters operate with the leading current, is achieved by opening the thyristors without time delay, and by closing them before the natural moment of their closing. We have carried out the analysis of electromagnetic processes in a static power current sourced converter with fully controlled thyristors according to a three-phase bridge circuit in the rectifier and dependent inverter modes, which can be used to build an intermediate DC link as components of flexible AC transmission systems with the capabilities of four-quadrant control of inter-system power exchange. We have created the conditions under which a three-phase bridge rectifier and a grid-controlled inverter with closing thyristors as a part of a direct current insert will not consume reactive power from the AC network, which is not provided for by the classical theory of their operation. The analytical expressions have been provided that can be used to obtain the basic energy characteristics of a DC insert made on the basis of current sourced converters, which not only does not need an additional resource of reactive power for its functioning, but can itself generate reactive power in an alternating current network. We have obtained analytical expressions for electromagnetic parameters, which can be the basis for further research and design of a prototype DC insert with new properties.
Regimes of DC link with gate turn-off thyristors
Keywords: перетворювач струму; інвертор; реактивна потужність; сurrent sourced converter; inverter; reactive power